PENINGKATAN KETERAMPILAN USAHA PRODUKSI MEDIA PENDIDIKAN MAHASISWA PROGRAM STUDI TEKNOLOGI PENDIDIKAN MELALUI PROGRAM MAGANG KEWIRAUSAHAAN DI PT. MATARAM INDAH - Haryanto, Haryanto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
The purpose of this program is to improve: (a) the knowledge of entrepreneurship ineducational  media· production,   (b)  technical   skill  in  education  media  production,  (c) entrepreneurial motivation, and (d) to develop collaborative networking with small industry in educational media production.The  internship  program  conducted  through  experiental  learning.  In  this  programstudents involved in the real process of media production and entrepreneurship. There are from activities: (a) Preparation. This activity is intended to give information about the process of entrepreneurship and educational media production, (b) Internship. In this activity students involve and learn the real process of entrepreneurship and production of educational media. (c) Evaluation. This activity is intended to evaluate the process and result of the program.The result of this program are: (a) 90% of students motivated to involve in industry of educational media, (b) 100% of students is able to make design of educational media in which each of them have one design, (c) The industry want expand and continue of the program in the next time, d) The lecturer know more about the real learning and model of teaching.Key words: educational media, and enterpreneurship internship.